The Relationship between Learning Motivation and Student Learning Outcomes - Siti Fatimatus Zahro (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2017)
The purpose of the research to determine whether there is a significant relationship between learning motivation and student learning outcomes. The kind of the research is correlational with quantitative approach. The subjects of the research are students of class VII at MTs Sunan Kalijaga Senduro. With the data collecting method that used is documentation, observation, and questionnaire. The data analysis method that used is quantitative with the formula is Pearson Product Moment. The results of the research there is a significant relationship between learning motivation and student learning outcomes.Keywords: learning motivation, and learning outcomes